2008
DOI: 10.1021/jf800267k
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Fusarium Toxin Levels in Corn Silage with Low Dry Matter and Storage Time

Abstract: Under unfavorable climatic conditions, Fusarium spp. can contaminate corn plants in the field and produce toxins that are present at the time of ensiling. The stability of deoxynivalenol, fumonisins B1 and B2, and zearalenone in corn silage was tested over two consecutive years. Variables studied were corn dry matter (DM) and storage length and temperature. The concentration of all Fusarium toxins decreased upon ensiling ( P < 0.001). Increasing the length of storage and ensiling with low DM resulted in a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
(30 reference statements)
1
23
1
Order By: Relevance
“…In contrast, most strains were capable to bind these toxins. In a following study (Boudra & Morgavi, 2008), the decrease in concentrations was in order deoxynivalenol > fumonisin B 1 > fumonisin B 2 > zearalenone in maize silage. The disappearance was significantly higher at a lower dry matter (280 vs. 420 g kg À1 ) and at prolonged storage (3 vs. 6 months), while the effect of temperatures, 15 or 30°C, was insignificant.…”
Section: Mycotoxinsmentioning
confidence: 81%
“…In contrast, most strains were capable to bind these toxins. In a following study (Boudra & Morgavi, 2008), the decrease in concentrations was in order deoxynivalenol > fumonisin B 1 > fumonisin B 2 > zearalenone in maize silage. The disappearance was significantly higher at a lower dry matter (280 vs. 420 g kg À1 ) and at prolonged storage (3 vs. 6 months), while the effect of temperatures, 15 or 30°C, was insignificant.…”
Section: Mycotoxinsmentioning
confidence: 81%
“…PH showed strong negative (P≤ 0.05) correlations with AFL (total) and ZEN. In the study by Boudra and Morgavi (2008) it was shown that some mycotoxins can be partially detoxified by the activity of silage fermentative bacteria. The disappearance of mycotoxins was significantly higher at a lower dry matter (280 vs. 420g kg -1 ) and at prolonged storage (3 vs. 6 months), while the effect of temperatures, 15 or 30°C, was insignificant (Kalač, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Their content is reduced by the activity of some lactic acid bacteria in the silage (Kalač, 2011). Boudra and Morgavi's (2008) results indicated that low dry matter at ensiling as well as prolonged storage could be a practical way to reduce or eliminate some Fusarium toxins in contaminated silages. However, there are other species, such as Aspergillus fumigatus, Penicillium roqueforti, P. paneum, F. oxysporum, and Monascus ruber that are able to tolerate both high levels of organic acids and carbon dioxide in addition to low availability of oxygen (Bryden, 2012;O'Brien et al, 2006;Storm et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Wet silage (below 30% DM; 31.8% of the samples) can lead to effluent production and eventual clostridial growth due to major water activity and organic acid dilution. In contrast, dry silage (above 35% DM; 27% of the samples) is predisposed to heating and mold growth (Boudra and Morgavi, 2008). The samples that showed the greatest concentrations for ZEA, DON, FB 1 , and FB 2 were 42.1, 36.3, 40.6, and 37.1% of DM, respectively; however, the lowest values were found at 33.1, 32.7, 29.0, and 33.7% of DM.…”
Section: Chemical Compositionmentioning
confidence: 99%